Pengembangan Produk Power Charger Portable dengan Menggunakan Metode Quality Function Deployment (QFD) - Rony Prabowo; Maulana Idris Zoelangga (Universitas Katolik Parahyangan, 2019)
Technological sophistication has become the necessity of human life, because it can facilitate the survival of human life. One of the technological sophistication that is needed by humans is the mobile phone. Mobile communication devices require electrical power sourced from the battery, when it runs out of power [1]requires a power source to restore power. Portable charger products [2]is one of the products that are always in need of mobile phone users. In this study, portable charger products have the advantage that can charge electric power just by moving it without using the electricity that comes from PLN. The purpose of this study is to determine the characteristics of portable charger products and designing products in accordance with the voice of customers obtained. In the first stage, the preparation and distribution of questionnaires to obtain voice of customer, create a technical response, create a house of quality, which then design the manufacture of portable charger products in accordance with customer wishes. Based on the research, the result of design of portable charger product with the length of 15 cm, width 8cm, thickness 3 cm and has the adhesive as long as 25 cm. Keywords: technology, phone, portable, charger, function